"Community Justice, " Ancestral Rights, and Lynching in Rural Bolivia. (January 2020) - Yates, Donna
Lynching in Bolivia has been portrayed as a largely routinized and primarily urban occurrence that is a direct response to the state's inability to provide security. Using a recent case of rural lynching as a starting point, I will evaluate the idea of rural Bolivian lynching in Indigenous communities as vigilantism. I contrast what little is known about rural lynching in Bolivia to the known pattern of urban lynching and ask whether these are distinct phenomena. Finally, I discuss the idea of ancestral validation and the punishment rights implied by a western-style state sanctioning aspects of non-western justice. I ask, do our existing models for such extreme cases as fatal vigilantism exclude lynching in rural Indigenous Bolivian communities? At the heart of this discussion is how we define a cultural practice versus how we define deviance in a multicultural society; how we nest authority structures and how we afford them legitimate rights to the use of force and other extreme control measures.